2014
DOI: 10.1074/jbc.m114.578393
|View full text |Cite
|
Sign up to set email alerts
|

G Protein Signaling Modulator-3 Inhibits the Inflammasome Activity of NLRP3

Abstract: Background: NLRP3 is a key regulator of innate inflammation and is linked to inflammatory diseases. Results: GPSM3 associates with NLRP3 and inhibits its function. Conclusion: GPSM3 specifically inhibits NLRP3-dependent inflammasome activity by interacting with its leucine-rich repeat domain. Significance: This association uncovers a putative new mechanism of NLRP3 control, linking a G protein modulator to NLRP3-dependent inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…However, many of the interacting SNPs are located near or within genes that may be involved in, or interfere with, mucosal barrier function (e.g. NOD2 , IRGM , CDH1 and GPSM3 36 ) or the adaptive immune response (e.g. IL2RA , CCL11 , CCL8 , MICB, IL10 and the HLA region).…”
Section: Discussionmentioning
confidence: 99%
“…However, many of the interacting SNPs are located near or within genes that may be involved in, or interfere with, mucosal barrier function (e.g. NOD2 , IRGM , CDH1 and GPSM3 36 ) or the adaptive immune response (e.g. IL2RA , CCL11 , CCL8 , MICB, IL10 and the HLA region).…”
Section: Discussionmentioning
confidence: 99%
“…This could alter the rate of degradation of AGS4/GPSM3 protein and could be one contributing factor leading to the inability to detect this protein in the kidney sections. For this reason, AGS4/GPSM3 has been largely studied in other cell types, particularly immune cells, due to its relatively high expression levels (Cao, Cismowski 2004, Billard, Gall 2014). Functionally, there is evidence that AGS4/GPSM3 couples to Gαi subunits to modulate agonist-dependent G-protein coupled receptor signaling (Oner, Maher 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, the biological relevance of Group I and II AGS in the kidney requires further investigation in genetically modified animal models. At present, mouse models that are genetically deficient for AGS1 (Cha, Kim 2013, Chen, Khan 2013, Cheng, Obrietan 2004), AGS3 (Regner, Nozu 2011, Blumer, Lord 2008), AGS4 (Giguere, Billard 2013, Giguere, Gall 2014), AGS5 (Konno, Shioi 2008) and AGS6 (Yang, Li 2013) are available, so there is opportunity exists to determine whether changes in the AGS gene expression can play a crucial role during various pathologies in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…126 Recent studies using a yeast twohybrid screen showed that the hematopoietic-restricted G protein signaling modulator-3 (GPSM3) interacts with NLRP3 and acts as a negative regulator of IL-1b production in response to NLRP3-dependent inflammasome activators. 127 In the screening of a kinase inhibitor library in another recent study, 3,4-methylenedioxy-b-nitrostyrene (MNS) was identified by the prevention of NLRP3-mediated ASC speck formation through targeting NLRP3 or NLRP3-associated complexes. 128 It is also noted that caspase-1, in spite of its essential role in the assembly of NLRP3 inflammasome, is found to play a critical regulatory role in house dust mite-induced allergic lung inflammation through downregulation of IL-33.…”
Section: Negative Regulation Of Nlrp3 Inflammasome Complex Activationmentioning
confidence: 99%